Securing UAV-Enabled Millimeter Wave Communication via Trajectory and Power Optimization - Wu, Yang; Yang, Weiwei; Sun, Xiaoli (2018 IEEE 4th International Conference on Computer and Communications (ICCC), 2018)
With many advantages such as high mobility, wide coverage and line of sight (LoS) channels, unmanned aerial vehicle (UAV) communication has drawn rising interest recently. However, the crowded microwave band can hardly meet the needs of high throughput in next generation (5G) networks, and the broadcasting nature of radiation makes UAVs prone to passive eavesdropping attacks. In this paper, we investigate the physical layer security (PLS) problem in UAV-Enabled millimeter wave downlink transmission, where one UAV communicates with a ground sensor while another UAV may intercept the communications between them. In contrast to the previous works, the UAVs' trajectory is extended to the three-dimensional (3D) space other than in a fixed altitude. The 3D sectorized antenna model is used to compare performance of directivity and gain, with which the concept of mobile secrecy guard cone (MSGC) is introduced to make the potential eavesdropper UAV remain outside the directional antenna beam during the flight. By applying block coordinate descent and successive convex optimization methods, an iterative algorithm is proposed to solve the non-convexity of the formulated problem. Simulation results show that our proposed algorithm performs significantly better than the benchmark methods.